Plant-Derived Iron Nanoparticles for Removal of Heavy Metals - Deepika Thilakan; Jaie Patankar; Srushti Khadtare; Nilesh S. Wagh; Jaya Lakkakula; Khalid Mohamed El-Hady; Saiful Islam; Md. Rabiul Islam; Mohd Shahnawaz Khan; Nouf Omar Alafaleq; Mohammad Tarique (International Journal of Chemical Engineering)
Nanoparticle synthesis has seen exponential development recently as its characteristics of high surface area, high rate of adsorption, and easy, cost-effective synthesis have been exploited for the purpose of ground water purification via the removal of organic and inorganic compounds, along with the removal of heavy metals and microbes. The synthesis of Zero-Valent Iron Nanoparticles (ZVI NPs) by green methods has proved to be environmentally friendly in many ways as it employs the use of naturally occurring plant extracts. These nanoparticles have large surface areas and efficiently remove heavy metals. The reducing potential of these ZVI NPs is mostly −0.44 V, thus allowing them to reduce heavy metal compounds such as cadmium, lead, zinc, copper, and arsenic present in wastewater. Irradiated nanoparticles have also exhibited antimicrobial resistance and adsorption. It is also observed that nanoparticles show a higher rate of efficacy at a lower pH. The adsorbent, which is ZVI NPs in this case, when present in large doses reduces heavy metal compounds rapidly and effectively.